A review of Paramaka Savage & Peters, 1992 (Ephemeroptera: Leptophlebiidae), with the description of two new species - Salles, F.f.; Domínguez, E.; Mariano, R.; Boldrini, R.; Clavier, S.; Lima, L. R. C. (Zootaxa, 2025)
Based on material from Brazil, Colombia, and French Guiana, two new species of Paramaka are described. The male imago of Paramaka lucimarae sp. nov. can be distinguished based on the following characteristics: abdominal color pattern uniformly tinged with orangish-brown; posteromedial projection of styliger plate short and not curved; telopenis base located at apical 2/3 of penis lobe; telopenis well developed and sclerotized, crossing medially, apex slightly expanded. The male imago of Paramaka takari sp. nov. can be distinguished based on the following characteristics: abdominal color pattern contrasting (segments I and VII or VIII to X darker, II to VI or VII translucent white); black medial marks on terga restricted to the anterior ½ (posterior segments) to ¼ (anterior segments); legs yellowish-white, except for apical black band on femora; posteromedial projection of styliger plate large and slightly curved at apex; and telopenis not sclerotized. Besides describing these new species, we present updated diagnoses, illustrations, distributional maps, and a key to nymphs and adults for all the species in the genus. Data is given based on fresh material of P. convexa and P. incognita and type-material of P. antonii, P. pearljam, P. incognita, and P. froehlichi.